Climate change: impact on the insurance industry - Yang, Qinshun (2024)
Background: Climate change can be identified as one of the major issues in front of society and businesses in the present time period. Climate change is resulting in natural calamities and diseases which can affect the sustainability of businesses across the globe. The insurance industry is also one of the major industries that has witnessed a significant number of changes due to climate change. In this regard, the research work is directed to explore some of the crucial and empirical impacts of climate change on the operational and structural framework of the companies operating in the insurance industry of Singapore.